Nanosized titanium dioxide-induced premature ovarian failure is associated with abnormalities in serum parameters in female mice - Hong F (Dove Medical Press, 2018)
Fashui Hong,1–4 Ling Wang5 1Jiangsu Collaborative Innovation Center of Regional Modern Agriculture and Environmental Protection, Huaiyin Normal University, Huaian, People’s Republic of China; 2Jiangsu Key Laboratory for Food Safety and Nutrition Function Evaluation, Huaiyin Normal University, Huaian, People’s Republic of China; 3Jiangsu Key Laboratory for Eco-Agricultural Biotechnology Around Hongze Lake, Huaiyin Normal University, Huaian, People’s Republic of China; 4School of Life Sciences, Huaiyin Normal University, Huaian, People’s Republic of China; 5Library of Soochow University, Suzhou, People’s Republic of China Background: Exposure to titanium dioxide nanoparticles (TiO2 NPs) that are widely used in food, medicine, sunscreen products and cosmetics is reported to cause ovarian damage and lower fertility in animals. However, the potential effects of TiO2 NPs application on premature ovarian failure (POF) have rarely been evaluated to date. Methods: In this study, female mice were continuously exposed to TiO2 NPs at doses of 2.5, 5 or 10 mg/kg via gavage instillation for 30 days, and investigated the serum hormones and autoimmunity markers associated with POF. Results: Exposure to TiO2 NPs resulted in POF, reductions in the levels of estradiol, progesterone and inhibin B and increases in luteinizing hormone, follicle-stimulating hormone, follicle-stimulating hormone/luteinizing hormone ratio, anti-Müllerian hormone, thyroid-stimulating hormone, free triiodothyronine, free tetraiodothyronine, anti-nuclear antibody and anti-thyroid peroxidase antibody levels in serum. Conclusion: Exposure to TiO2 NPs induced POF triggered by alterations in hormones and autoimmunity markers. Our findings highlight the necessity for significant caution in handling and usage of TiO2 NPs by female consumers. Keywords: titanium dioxide nanoparticles, mice, premature ovarian failure, serum hormone levels, autoimmunity levels